Silk nano‐discs: A natural material for cancer therapy1. Issue 11 (5th December 2018) - Patwa, Rahul; Soundararajan, Narendren; Mulchandani, Neha; Bhasney, Siddharth M.; Shah, Manisha; Kumar, Sachin; Kumar, Amit; Katiyar, Vimal
Abstract: The article demonstrates the crystalline silk nano‐discs (CSNs), with well‐controlled morphology, which upon magnetization, yields magnetic crystalline silk nano‐discs, making both prominent alternatives for replacing metal templates such as gold, silver, and so on in therapeutics and implants. The isolated β‐sheet‐rich discotic CSNs have ~50 nm diameter, high crystallinity (> 90%), and are insoluble but provide good dispersibility and stability in aqueous solutions. The melt blending‐cum‐electrospinning of functionalized CSN with poly(lactic acid) results in biocompatible nanofiber‐based scaffolds having in vitro cell cytocompatibility with improved cell adhesion and proliferation. The assessment of release behavior of curcumin, a naturally occurring anticancer drug, shows sustained release over 25 days exhibiting effective cytotoxicity against human cervical cancer cells. Further, combined effect of curcumin and hyperthermia reduced the cell growth by ~63%. Alignment of CSN‐derived magnetic nanoparticles due to effective fiber drawing process during electrospinning could improve cytocompatibility against BHK‐21 cells, and therefore efficacy for cancer therapy. Abstract :